Data-driven learning for the next generation corpora and DDL for pre-tertiary learners - Crosthwaite, Peter (Abingdon, Oxon, [England] Routledge, an imprint of the Taylor & Francis Group, 2020)
"Despite advancements in and availability of corpus software in language classrooms facilitating data-driven learning (DDL), the use of such methods with pre-tertiary learners remains rare. This book explores the affordances of DDL specifically for younger learners, testing its viability with teachers and students at the primary and secondary years of schooling. It features eminent and up-and-coming researchers from Europe, Asia, and Australasia who seek to address best practice in implementing DDL with younger learners, while providing a wealth of empirical findings and practical DDL activities ready for use in the pre-tertiary classroom. Divided into three parts, the volume's first section focuses on overcoming emerging challenges for DDL with younger learners, including where and how DDL can be integrated into pre-tertiary curricula, as well as potential barriers to this integration. It then considers new, cutting-edge innovations in corpora and corpus software for use with younger learners in the second section, before reporting on actual DDL studies performed with younger learners (and their teachers) at the primary and secondary levels of education. This book will appeal to post-graduate students, academics and researchers with interests in corpus linguistics, second language acquisition, primary and secondary literacy education, and language and educational technologies"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Corpora (Linguistics) -- Data processing; Computational linguistics; Language and languages -- Computer-assisted instruction; Second language acquisition